Long-term follow-up after percutaneous closure of patent foramen ovale with Amplatzer PFO Occluder: a single center experience - Araszkiewicz, Aleksander; Grygier, Marek; Iwańczyk, Sylwia; Trojnarska, Olga; Lesiak, Maciej; Grajek, Stefan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction : Patent foramen ovale (PFO) is associated with the occurrence of cryptogenic strokes, transient neurological ischemic attacks (TIA) and migraine. Therefore despite the recent ambiguous results of prospective controlled trials, percutaneous closure of PFO is still performed in many centers. Aim : To evaluate the safety and effectiveness of percutaneous PFO closure in the prevention of recurrence of neurologic events and migraine symptoms in long-term observation. Material and methods : In 70 patients (31 male, age: 38 ±18 years) percutaneous PFO closure was successfully performed with the Amplatzer PFO Occluder. An interview in conjunction with neurological follow-up was performed in all patients to reveal recurrence of embolism such as TIA or stroke and the presence of migraine symptoms before and after the procedure. Results : The mean follow-up period was 857 ±363 days (median: 571 days). No serious complications of the procedure and no death were observed. Neurological events recurred in 5 (7.1%) patients – stroke in 1 patient, TIA in 3 patients, ocular embolism in 1 patient. All of these patients were over 40 years old or had other cardiovascular risk factors. Migraine was observed in 21 (30%) patients before the procedure and in 11 (15.7%) after the procedure (p = 0.04). Conclusions : The complication rate and recurrence of neurological events in young patients after PFO closure are low. However, careful qualification and postprocedural monitoring of the patients are necessary. Patent foramen ovale closure seems to result in attenuation of migraine symptoms.